Development of Deflection Angle Stabilizing System for Balancing Robot - Fedorov, Dmitry; Ivoilov, Andrey; Zhmud, Vadim; Trubin, Vitaly (Journal of Advances in Management Sciences & Information Systems, 2015)
This paper performs determination of a mathematical model of the balancing robot, its linearization and algorithm for calculation of stabilization of the deflection angle from the vertical modal method. This algorithm also makes determination of the angle of deviation from the use of either alpha-beta filter and the angle of rotation of the wheels by means of encoders.